Concern for Relative Standing and Deception - Spyros Galanis; Michael Vlassopoulos (Institute for the Study of Labor (IZA), 2014)
We report results from a sender-receiver deception game, which tests whether an individual's decision to deceive is influenced by a concern for relative standing in a reference group. The sender ranks six possible outcomes, each specifying a payoff for him and the receiver. A message is then transmitted to the receiver, announcing that the sender has ranked the outcomes according to the receiver's payoff, from highest to lowest. The receiver, without knowing that there is conflict of interest, chooses an action that determines the payoff of both players. The sender has an incentive to deceive the receiver, in order to obtain a higher payoff. A sender is positively biased if he thinks that he is higher in the deception distribution than in reality. We show theoretically that a positively biased sender will increase cheating when presented with information about the deception of his peers. The experimental data confirm this. We conclude that concern for relative standing does play a role in the decision to deceive.
Keywords: C91; D03; D83; 330; deception; lying; sender-receiver game; concern for rank